Isolation of Ferulic Acid from Leaves of Mindi (Melia azedarach L.) and Its Antioxidant Activity Test - Andriyani Budi Listyo; Dewi Kusrini; Enny Fachriyah (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
Mindi (Melia azedarach L.) is one of a plant from Meliaceae family and has been known for its bioactive compound, such as ferulic acid. On this study, the isolation of ferulic acid and antioxidant activity test has been conducted. The aim of this study was to isolate the ferulic acid on ethanol extract of Melia azedarach L. leaves, determine the ferulic acid content and antioxidant activity test qualitatively. The method used in this research was isolation with hydrolysis (acid and base) and without hydrolysis, determining the phenolic acid content using TLC scanner instrument and antioxidant activity test qualitatively using DPPH radical reduction method. According to the identification using TLC and TLC scanner, the base hydrolysis fraction (HB), acid hydrolysis (HA), and without hydrolysis (HA) of ethanol extract from Melia azedarach L. was suspected contain the ferulic acid compound. The analysis result using TLC scanner was known to have ferulic acid content on HB, HA, and TH fraction of 15.57%,12.17%, and 9.56%, respectively. This study showed that hydrolysis affected the phenolic acid content where the HB fraction produced higher ferulic acid than HA and TH fraction. The antioxidant activity test that has been conducted qualitatively showed that ferulic acid isolates contained on each fraction actively reduce the DPPH radical.